Multiplicity of Nontrivial Solutions for Kirchhoff Type Problems. (22nd December 2010) - Cheng Cheng, Bitao Bitao; Wu Wu, Xian Xian; Liu Liu, Jun Jun
Abstract : By using variational methods, we study the multiplicity of solutions for Kirchhoff type problems − ( a + b ∫ Ω | ∇ u | 2 ) Δ u = f ( x, u ), in Ω ; u = 0, on ∂ Ω . Existence results of two nontrivial solutions and infinite many solutions are obtained.